All‐Transparent Oxide Photovoltaics: AZO Embedded ZnO/NiO/AgNW Band Selective High‐Speed Electric Power Window. (7th August 2019) - Ban, Dong‐Kyun; Patel, Malkeshkumar; Nguyen, Thanh Tai; Kim, Joondong
Abstract: Electric power windows using an all‐transparent oxide photoelectric device have the potential to shield and exploit ultraviolet radiation. Herein, an Al:ZnO embedded large area all‐transparent ZnO/NiO electric power window is presented. A large‐scale (1‐in. square) device fabricated with the structure of FTO/AZO/ZnO/NiO/AgNW exhibits a visible light transmittance >70% and photovoltaic performance with an enhanced power conversion efficiency of 3.13% under UV illumination (λ = 365 nm). The spectral attributes of this heterostructure are analyzed using I–V plots, photoresponse, and photo‐carrier lifetime (τ), which reveal the co‐occurrence of photovoltaic and pyro‐phototronic effects, and τ value tuning from 9 to 38.5 ms by tuning λs. The device exhibits higher efficiency at a λ of 410 nm due to exciton attributed optoelectronics at room temperature. Further, the device demonstrates a 380% enhanced photocurrent value, with speed of <40 µs. The functional use of AZO‐based back surface field would improve transparent photovoltaics which can be applied to the on‐site power generation of building windows, and protect human beings from harmful UV exposure. It is suggested that the formation of a back‐surface field is required to enhance the underlying performance of all‐transparent oxide photo‐electronics, including solar cells, photodetectors, sensors, and memory devices. Abstract : All‐transparent oxide photovoltaics device with transparency >70% demonstrates tunable optoelectronics performance. Back surface field formation is the key to efficient optoelectronics, and the device offers co‐occurrence of photovoltaics and a pyro‐phototronic effect, high‐speed, wavelength tunable minority carrier lifetime and photoresponse.